Our Public Health History in Florida: Interview with Laurence G. Branch - Robert J. McDermott (University of North Florida, 2005)
Laurence G. Branch, PhD became the third Dean of the University of South Florida College of Public Health, and served in that capacity from 2002 to 2003. Before coming to USF he was a Research Professor at Duke University's Center for the Study of Aging and Human Development (1995-2002), and also the Director of Duke's MD-MPH Program and Director of its Long-Term Care Research Program. He also has held faculty appointments at Harvard Medical School and Harvard School of Public Health (1978-1986), at Boston University School of Medicine (1986-1996), and an adjunct appointment at Tufts University School of Medicine (1984-1992). He contributes regularly to the health policy field as evidenced by his more than 150 articles in peer-reviewed journals and over 50 book chapters and monographs. He currently is the co-editor of the Journal of Aging and Health. Formerly, he was editor-in-chief of The Gerontologist. He is a member of the editorial boards of two other professional journals, and reviews for several additional scholarly publications. The Gerontological Health Section of the American Public Health Association honored him in 2003 by naming the annual award for best doctoral research, the Laurence G. Branch Student Research Award. Dr. Branch's research responsibilities past and present include being Director of the Massachusetts Health Care Panel Study (1974-present), Director of the Disability Sub-study of the Framingham Heart Study (1976-1980), and a co-investigator of the East Boston EPESE study for the National Institute on Aging (1982-1989). He also was responsible for the evaluation of the On Lok replications (1991-1995). His experiences in government and in the health care industry are also extensive. This interview took place between April 3, 2005 and May 8, 2005.